(Solid + liquid) phase equilibria of (Ca(H2PO2)2 + CaCl2 + H2O) and (Ca(H2PO2)2 + NaH2PO2 + H2O) ternary systems at T = 323.15 K. (February 2016) - Cao, Hong-yu; Zhou, Huan; Bai, Xiao-qin; Ma, Ruo-xin; Tan, Li-na; Wang, Jun-min
Graphical abstract: Solubility diagram of the (Ca(H2 PO2 )2  + NaH2 PO2  + H2 O) system at T  = (323.15 and 298.15) K. Highlights: Phase diagrams of Ca 2+ -H2 PO2 − -Cl − -H2 O, Ca 2+ -Na + -H2 PO2 − -H2 O at 323.15 K were obtained. Incompatible double salt of NaCa(H2 PO2 )3 in Ca 2+ -Na + -H2 PO2 − -H2 O system was determined. Density diagram of the corresponding liquid were simultaneously measured. Abstract: Calcium hypophosphite has been widely used as an anti-corrosive agent, flame retardant, fertilizer, assistant for Ni electroless plating, and animal nutritional supplement. High purity calcium hypophosphite can be synthesized via the replacement reaction of sodium hypophosphite and calcium chloride. In this work, the (solid + liquid) phase equilibria of (Ca(H2 PO2 )2  + CaCl2  + H2 O) and (Ca(H2 PO2 )2  + NaH2 PO2  + H2 O) ternary systems at T  = 323.15 K were studied experimentally via the classical isothermal solubility equilibrium method, and the phase diagrams for these two systems were obtained. It was found that two solid salts of CaCl2 ·2H2 O and Ca(H2 PO2 )2 exist in the (Ca(H2 PO2 )2  + CaCl2  + H2 O) system, and three salts of Ca(H2 PO2 )2, NaH2 PO2 ·H2 O and one incompatible double salt, NaCa(H2 PO2 )3 occur in the (Ca(H2 PO2 )2  + NaH2 PO2  + H2 O) system.